STRATEGI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENANAMKAN NILAI-NILAI KARAKTER PADA SISWA (STUDI MULTI KASUS DI SDI RAUDLATUL JANNAH SIDOARJO DAN SDIT GHILMANI SURABAYA) - Afifah Afifah; Imam Mashuri (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
The purpose of this study first, to describe the character values ​​implanted by teachers of PAI on students in SDI Raudlatul Jannah Sidoarjo and SDIT Ghilmani Surabaya. Second, describe the strategy of PAI teachers in instilling the character values ​​of students in SDI Raudlatul Jannah Sidoarjo and SDIT Ghilmani Surabaya. Third, describe the process of internalization of character values ​​on students in SDI Raudlatul Jannah Sidoarjo and SDIT Ghilmani Surabaya. This research uses qualitative approach with descriptive technique of descriptive informant. Data collection techniques with participant observation, in-depth interviews, and documentation analysis. The results of this study conclude that in the inculcation of the values ​​of character education in the students the teacher has a special strategy by applying his role as educator, lecturer, curriculum developer, reformer, model and role model in integrating character values ​​into the whole subjects, day, school programs, and building cooperation between schools with parents. Keywords: Strategy, Islamic Religious Education Teachers, Character